Impact of the first wave of coronavirus disease 2019 (COVID-19) pandemic on the diagnosis of heart disease in the Russian Federation: results from the Russian segment of the IAEA INCAPS COVID study - A. A. Ansheles; V. B. Sergienko; V. E. Sinitsyn; M. N. Vakhromeeva; A. N. Kokov; K. V. Zavadovsky; D. V. Ryzhkova; A. V. Karalkin; I. V. Shurupova; V. A. Pospelov; E. V. Migunova; G. B. Sayfullina; et al. (Российский кардиологический журнал, 2021)
Aim. To assess the impact of the first wave of coronavirus disease 2019 (COVID-19) pandemic on the diagnosis of heart disease in the Russian Federation.Material and methods. Fifteen Russian medical centers from 5 cities took part in an online survey organized by the Division of Human Health of the International Atomic Energy Agency (IAEA), containing questions regarding alterations in cardiovascular procedure volumes resulting from COVID-19 in March-April 2020.Results. A number of outpatients undergoing cardiac diagnostic procedures was noted in 80% of clinics. Cardiovascular procedure volumes in the period from March 2019 to March 2020 in general decreased by 9,5%, and from March 2019 to April 2020, by 56,5%. Stress electrocardiography decreased by 38,4%, stress echocardiography by 72,5%, stress single-photon emission computed tomography by 66,9%, computed tomography angiography by 49,7%, magnetic resonance imaging by 42,7%, invasive coronary angiography by 40,7%. The decrease in diagnostic procedure volumes in selected regions (Tomsk Oblast, Kemerovo Oblast, Tatarstan) was not so pronounced compared to Moscow and St. Petersburg (-20,7%, -75,2%, -93,8% in April 2020, respectively, p<0,001).Conclusion. The first wave of the COVID-19 pandemic caused a sharp decrease in the number of diagnostic cardiac procedures in Russia. This has potential longterm implications for patients with cardiovascular disease. Understanding these implications can help guide diagnostic strategies during the ongoing COVID-19 pandemic and minimize the future losses.